Development of Discovery Learning-Based Chemistry Learning E-Modules on Atomic Structure Materials to Improve Learning Outcomes of Class X Students - Purba, Windi Sahayani; Kembaren, Agus (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This research aims to develop a chemistry-based e-module based on Discovery Learning on Atomic Structure material and to determine its feasibility, practicality, and effectiveness in improving the learning outcomes of class X students of SMA Negeri 13 Medan. The type of research used is Research and Development (R&D) with the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation stages . The research subjects consisted of expert validators and students of class X of SMA Negeri 13 Medan. The research instruments used included expert validation sheets, student response questionnaires, and pre-test and post-test questions. Data were analyzed using percentage descriptive analysis and N-Gain test. The results of the study showed that the e-modules developed obtained an average feasibility percentage of 82.20% with the category "Very Feasible", based on the assessment of subject matter experts of 79.76%, media experts of 84.03%, and learning experts of 82.81%. The level of practicality of the e-module based on the response of students obtained an average percentage of 84.73% with the category of "Very Practical". In addition, e-modules have proven to be effective in improving student learning outcomes, as shown by an increase in the average pre-test score of 40.67 to 83.53 in the post-test, with an average N-Gain Score of 0.73 which is in the high category. All students experienced an increase in learning outcomes after using the e-module. Based on the results of the research, it can be concluded that the chemistry learning e-module based on Discovery Learning on the Atomic Structure material developed is very feasible, practical, and effective to be used in chemistry learning class X of SMA Negeri 13 Medan.